PSIKOEDUKASI UNTUK MEMPERKUAT SUPPORT SYSTEM PEMAIN FUTSAL KOMUNITAS “OR” DI KOTA S LATAR LAYANAN KOMUNITAS - Muhammad Asykur Rois; Herlan Pratikto (PT. Hasba Edukasi Mandiri, 2025)
Futsal communities as team-based sports require not only physical and technical skills but also adequate psychological support to maintain performance and athletes’ well-being. One important psychological factor in this context is the support system, which includes emotional, informational, instrumental, and esteem support. This study aims to describe the implementation of psychoeducation in strengthening the support system of futsal players in the “OR” community in City S. The study employed a qualitative approach with a community-based psychological service design. Participants included futsal players, a coach, and community administrators. Data were collected through observation, semi-structured interviews, and Focus Group Discussions (FGD). The psychoeducational intervention was conducted in two sessions using interactive lectures, group discussions, self-reflection, and role-play simulations of competitive pressure. The results indicated an increased understanding of the importance of support systems, improved supportive communication, and enhanced empathy and team cohesion. Psychoeducation proved to be an effective approach to strengthening social support and promoting psychological well-being and team performance in a community futsal setting.